Effects of Seahorse Supplementation for 6 Weeks on Muscle Mass, Muscle Fitness, and Exercise Performance Abilities in Elderly - Byeong Hwan Jeon (Asian Society of Kinesiology, 2019)
OBJECTIVES Base on the series of findings for seahorse supplementation of our group, we were supposed to investigate the effects of seahorse extract supplementation for 6 weeks on muscle mass, muscle fitness, and the ability of daily life and exercise performance in elderly. METHODS The elderly were divided into SHD(seahorse diet, n=27) and CON(control, n=26) group and supplemented with 1,000 mg / day of seahorse extract for 6 weeks. Before and after 6 week of treatments, they were observed changes in body composition and muscle mass, muscle strength and endurance, the exercise performance abilities including cardiac function and autonomic nervous system activity, static and dynamic stabilities, and blood variables. RESULTS After the 6 week of seahorse supplementation in elderly, 1) it has been shown the quantitative and qualitative improvement within muscle by increased total lean body(muscle) mass, weight bearing muscle endurance, isokinetic muscle endurance; 2) An in static stability showed improved by increased in one leg standing time. A decrease in heart rate and an increase in SDNN showed partial improvement of the autonomic nervous system; 3) There was partial improvement on the blood metabolism functions by a decrease in blood lactate levels and an increase in HDL cholesterol. CONCLUSIONS These changes suggest that the 6-week of seahorse supplementation may improve in muscle mass and fitness, and the ability of daily life and exercise performance in elderly.